Language economy and the pro-drop theory from a minimalist perspective - Corbara, Erika (Bohemica Olomucensia, 2014)
This paper aims at a new reconsideration of the pro-drop theory, focusing on the properties and requirements of language economy principles, whose satisfaction constitutes the central point of the Minimalist program (MP). Starting and fundamental approach of the research is the consideration of the language faculty as a biological system of the human being: The pro-drop languages (PDL) and their syntactic and semantic features will be thus investigated from a strongly minimalist point of view in order to find a clearer and cross-linguistic explanation of the pro-drop phenomenon.